A Study of Factors Influencing Online Purchasing Intention within E-tourism Setting - MORADI, Leila; YAHYA, Yazrina; MOHAMED, Ibrahim; RAISIAN, Komeil (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).18, 2017)
Tourism is considered as significant issue in the economy of Malaysia. Online channels usually offer great opportunities for customers to get relevant information regarding the e-tourism and technology. Tourism websites are considered as the fundamental principles in attracting more tourists. However, purchase intention through websites is not only dependent on the website characteristics, but it also depends on consumer-related factors like experience that might affect the purchasing intention. This study proposes and validates a model that aggregate two facets namely, website and consumer-side factors in conjunction with purchasing intention from tourism websites. Findings of the study shows that website and consumer factors strongly associates with purchasing intention from tourism websites. Website navigability and security (website characteristics, as well as experience (consumer-side factor) are proven to have effect on the purchasing behaviors of tourists. However, website quality does not interact with purchasing intention. Furthermore, the study signifies that only high quality website cannot ensure continuance purchasing behavior. Consequently, underlying factors such as information richness and trust need further investigation.